PERANCANGAN SISTEM INFORMASI OBJEK WISATA DI KABUPATEN BENGKULU UTARA BERBASIS WEB - Yopita Syaputri; Kirman Kirman; Anisya Sonita; Dedy Agung Prabowo (Jurnal Media Infotama, 2024)
A design ofweb-based information system oftourism objects in north Bengkulu regency is used as a tool in delivering information on tourism and cultural areas in north Bengkulu regency to people who want to know the tourism areas. It is one form of tourism promotion to attract tourists to visit north Bengkulu. This research is expected to be useful as a medium of information and promotion of tourismpotential in north Bengkulu, so that people will be more familiar with regional tourismplaces. The more tourists who visit, the income of the area and the surrounding community will increase. The method used in this research was the Rapid Application Development (RAD) method. This method includedthe requirements analysis, system design, implementation, testing and maintenance stages, followed by making applications using the PHP and HTML programming languages with MySQL and XAMPP database